REPRODUCTIVE EFFICIENCY OF DESERT SHEEP FOLLOWING SURGICAL INTRAUTERINE ARTIFICIAL INSEMINATION IN THE SUDAN - Nour, Mohamed; S, M.; Musa; M, S.; A Makawi, S. (Journal of Veterinary Medicine and Animal Production, 2022)
The objective of the present study was to verify the competence of intra-uterine Artificial Insemination via surgical interference using fresh diluted semen in improving reproductive performance in Desert ewes compared to the conventional methods. Thirty Hamari ewes were selected with average age of 27 months, body weight of 30 kg and body condition score of 3 . They were equally divided into 3 groups (10 ewes each). The three groups were randomly assigned to intra-uterine artificial insemination (IUAI), intra-cervical artificial insemination (ICAI) and natural mating (NM). Oestrus was synchronized and induced in all ewes using progesterone and pregnant mare serum gonadotrophin (PMSG). The ewes were fitted with controlled internal drug releaser (CIDR, 0.3 g progesterone) for 12 days. At the time of CIDR withdrawal, ewes received 300 IU of PMSG intramuscularly. Artificial insemination (IUAI & ICAI) was performed using freshly collected semen diluted in reconstituted skim powdered milk. Intra-uterine artificial insemination was conducted 50-54 hours post PMSG treatments, while the intra-cervical insemination was conducted at heat detection after progesterone and PMSG treatment. Ewes assigned for natural mating were left with the ram just after the hormonal treatment. Most of the ovulatory follicles in ewe’s undergone surgery were found in the right ovary (80%) with a diameter ranged between 0.5 to 0.8 cm. The conception rate as detected by the non-return rate using a vasectomized ram and confirmed by progesterone assay was significantly higher (p <0.001) for ewes undergone intra-uterine insemination (100%) and natural mating (100%) compared to cervical insemination (60%). In contrast, the lambing rate of the ewes undergone surgical intra-uterine insemination was significantly lower (p< 0.001) as compared to ewes inseminated intra-cervically or naturally mated. There was a significant difference in the twining rate for ICAI and NM (66.7% and 16.7%, respectively) whereas no twins were born by ewes undergone IUAI. There were no significant differences (P>0.05) in litter size and gestation length for all types of insemination. In conclusion, the present results indicate that the intra-uterine artificial insemination was an efficient method in ewes to achieve high conception rates; as shown by the non-return rate , despite the low lambing rate .However, a suitable less stressful methods such as laparoscopic insemination could be used in future studies